Hip Fractures in Centenarians: Has Care Improved in the National Hip Fracture Database Era?. (September 2017) - Dick, Alastair G.; Davenport, Dominic; Bansal, Mohit; Burch, Therese S.; Edwards, Max R.
Introduction: The number of centenarians in the United Kingdom is increasing. An associated increase in the incidence of hip fractures in the extreme elderly population is expected. The National Hip Fracture Database (NHFD) initiative was introduced in 2007 aiming to improve hip fracture care. There is a paucity of literature on the outcomes of centenarians with hip fractures since its introduction. The aim of this study is to report our experience of hip fractures in centenarians in the era since the introduction of the NHFD to assess outcomes in terms of mortality, time to surgery, length of stay, and complications. Methods: A retrospective case note study of all centenarians managed for a hip fracture over a 7-year period at a London district general hospital. Results: We report on 22 centenarians sustaining 23 hip fractures between 2008 and 2015. Twenty-one fractures were managed operatively. For patients managed operatively, in-hospital, 30-day, 3-month, 6-month, 1-year, 2-year, 3-year, and 5-year cumulative mortalities were 30%, 30%, 39%, 50%, 77%, 86%, 95%, and 100%, respectively. In-hospital mortality was 100% for those managed nonoperatively. Mean time to surgery was 1.6 days (range: 0.7-6.3 days). Mean length of stay on the acute orthopedic ward was 23 days (range: 2-51 days). Seventy-one percent had a postoperative complication most commonly a hospital-acquired pneumonia or urinary tract infection. Conclusion: Compared to a series of centenarians with hip fractures prior to the introduction of the NHFD, we report a reduced time to surgery. Mortality and hospital length of stay were similar.